COVID-19: MENGUKUR KEPUASAN MAHASISWA YANG MENGGUNAKAN TELECONFERENCE DALAM PEMBELAJARAN - Ikhlash, Muhammad; Halim, Muhammad Irsyad; Warga Dalam, Winanda Wahana; Sihombing, Ronaldo Antonius (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2021)
This study aims to test empirically whether the quality of the system, the quality of information, and the ease of use of the teleconference system used by students in learning during the Covid-19 pandemic influence student satisfaction in using the system. The sample in this study were students who used the teleconference system in learning during the Covid-19 pandemic, totaling 356 people. The test tool in this study uses validity, reliability, and hypothesis testing. Based on the research results, it was found that the quality of the teleconference system had a significant effect on student satisfaction in using the system. The quality of information from the teleconference system has a significant effect on student satisfaction in using the system. The ease of using the teleconference system has a significant effect on student satisfaction in using the system.